Persepsi Tentang Manfaat Yoga Prenatal untuk Meningkatkan Kesiapan Menghadapi Persalinan pada Ibu Hamil di PMB Jaba Denpasar: Studi Kualitatif - Kadek Sri Ariyanti; Made Dewi Sariyani; Siti Zakiah; I Nyoman Dharma Wisnawa (UHN IGB Sugriwa Denpasar, 2022)
Pregnancy causes physical and psychological changes. Changes that occur in pregnant women cause physical discomfort such as back pain, cramps and swelling, as well as psychological changes such as anxiety in facing childbirth. The Covid-19 pandemic condition causes psychological problems for pregnant women such as anxiety to come to health services. One of the interventions that can be done to reduce the complaints, discomfort and anxiety experienced by pregnant women in this new normal era is physical exercise, such as meditation/yoga. Prenatal yoga is believed to be able to reduce physical complaints and anxiety of pregnant woen in the face of childbirth. This study aims to explore the perception of pregnant women about the benefits of prenatal yoga. The research design used is qualitative with a phenomenological approach. The research location was at PMB Jaba Denpasar, in April 2022. The informants in this study were third trimester pregnant women who did prenatal yoga with a total of 10 people. For data validation, researchers used key informants, namely midwives and husbands of pregnant women. Data processing is carried out through several stages, namely: reduction, data presentation and drawing conclusions. The results showed that pregnant women's perceptions of the benefits of prenatal yoga include: 1) Reducing physical complaints; 2) Reduce anxiety; 3) Increase readiness in facing childbirth. It is necessary to improve the implementation of prenatal yoga in the implementation of ANC, so that the benefits can be felt by pregnant women in order to reduce maternal and infant morbidity and mortality.